Energy storage for sustainable microgrid - Gao, David Wenzhong (Academic Press is an imprint of Elsevier, 2015)
Energy Storage for Sustainable Microgrid addresses the issues related to modelling, operation and control, steady-state and dynamic analysis of microgrids with ESS. This book discusses major electricity storage technologies in depth along with their efficiency, lifetime cycles, environmental benefits and capacity, so that readers can envisage which type of storage technology is best for a particular microgrid application. This book offers solutions to numerous difficulties such as choosing the right ESS for the particular microgrid application, proper sizing of ESS for microgrid, as well as.